Interactions of body representations in rubber hand illusion and tool-use paradigms - Erkent, Mahmut Alp. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
In neuropsychological literature, numerous case studies suggest two separate body representations in the brain; one for perception, called the body image, and one for action, called the body schema. Rubber hand illusion and tool-use paradigms have been used frequently to investigate these body representations, respectively. Although these experimental paradigms are thought to affect different body representations, interactions between them are inevitable, considering the common sensory modalities targeted by the techniques used for measuring their effects. Still, there has been minimal overlap between these related fields of study. In this thesis, we combined these paradigms in a novel experimental setup and comparatively examined the resulting changes in body representations. Specifically, after a tool-use task where subjects actively used a grabber tool with their right hand to move cubes close to or away from their body, we observed an increase in the metric representation of the right forearm length depending on the length of the tool used. Subsequently, the “tool-holding” rubber hand illusion also increased the forearm length representation if the subject saw a longer tool held by the rubber hand. Follow-up experiments showed that this effect in rubber hand illusion depends on prior active use of the tool, embodiment of the observed hand and tool, and a length disparity between the held and observed tools during RHI. Overall, these results reveal for the first time that the representation of forearm length, a component of body schema, can be modified through changes in body image.
Keywords: Neuropsychological tests.